2013
DOI: 10.3389/fnhum.2013.00068
|View full text |Cite
|
Sign up to set email alerts
|

Short-interval intracortical inhibition is not affected by varying visual feedback in an isometric task in biceps brachii muscle

Abstract: Short-interval intracortical inhibition (SICI) of the primary motor cortex (M1) appears to play a significant role in skill acquisition. Consequently, it is of interest to find out which factors cause modulation of SICI.Purpose: To establish if visual feedback and force requirements influence SICI.Methods: SICI was assessed from 10 healthy adults (5 males and 5 females aged between 21 and 35 years) in three submaximal isometric elbow flexion torque levels [5, 20, and 40% of maximal voluntary contraction (MVC)]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 35 publications
(63 reference statements)
2
21
0
Order By: Relevance
“…Following the familiarisation session, all participants completed a 1-RM strength, and then were matched for gender and baseline strength, then randomly allocated into either the control (no training) or training group. A purpose made Excel macro was used to randomize participants based upon baseline strength and gender (Rantalainen et al 2013). All participants underwent TMS and maximum strength testing of the right and left biceps brachii and flexor carpi radialis before and after a three week supervised strength-training program of the right elbow flexors with post-testing occurring within 48 hours of the final training session.…”
Section: Experimental Approachmentioning
confidence: 99%
“…Following the familiarisation session, all participants completed a 1-RM strength, and then were matched for gender and baseline strength, then randomly allocated into either the control (no training) or training group. A purpose made Excel macro was used to randomize participants based upon baseline strength and gender (Rantalainen et al 2013). All participants underwent TMS and maximum strength testing of the right and left biceps brachii and flexor carpi radialis before and after a three week supervised strength-training program of the right elbow flexors with post-testing occurring within 48 hours of the final training session.…”
Section: Experimental Approachmentioning
confidence: 99%
“…This may be indicative of plastic or physiological changes regarding the availability and transmission of the neurotransmitter GABA, or the action of baclofen that facilitates GABAB activity [3,6] . However, these inhibitory networks are speculated to play a role in movement regulation and behavior in both healthy and diseased states [18][19][20][21][22] . These inferences, together with novel information obtained in our recent study [7] , allow for interpretation of how intracortical inhibition is linked to some of the motor symptoms that are prominent following SCI.…”
Section: Discussionmentioning
confidence: 99%
“…The influences of voluntary drive on intracortical inhibition within M1 described above may allow some inference of the impact that altered inhibition following SCI has on motor symptoms and behavior. For example, work by Rantalainen and colleagues [21] demonstrated that SICI plays a role in force gradation. They measured SICI of the biceps under a number of different levels of tonic contraction and found that SICI was present at low submaximal force levels but became significantly reduced at higher force levels.…”
Section: Alterations To Motor Behavior In Spinal Cord Injurymentioning
confidence: 99%
“…When humans voluntarily activate a muscle, the magnitude of short-interval intracortical inhibition (SICI) decreases (Ridding et al, 1995;Rantalainen et al, 2013;Sharples and Kalmar, 2012;Ortu et al, 2008). It is thought that inhibitory intracortical circuits modulate the excitability of the cortical neurons that project to the spinal motor neurons of the muscles involved in the task (Reis et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that inhibitory intracortical circuits modulate the excitability of the cortical neurons that project to the spinal motor neurons of the muscles involved in the task (Reis et al, 2008). The degree of reduction in intracortical inhibition is related to contraction intensity (Rantalainen et al, 2013;Ortu et al, 2008), contraction type (Howatson et al, 2011), and whether the movement starts or ends (Sidhu et al, 2013). SICI is also modulated during postural contractions, defined as contractions with the aim to maintain a certain posture, as shown by a reduction in SICI in the soleus muscle during standing as compared with sitting (Soto et al, 2006).…”
Section: Introductionmentioning
confidence: 99%